Interpretative Considerations about the love as concept within the Social World - Forero Perdomo, Nathalie (2021)
The aim of this research is to offer interpretative considerations for the understanding of the concept of love within the social world. The text addresses love from a historical dimension that crosses the classical Greek conception, passing through the approach to Christian love and its constitutive elements, to put forward ideas of heteropatriarchal love and the feminist perspective of love as a critical emancipatory and transformative proposal of the social order. This research begins with the relationship between emotion and reason with an example of the close link between the individual and his community in the construction of values, habits and symbolic codes that harmoniously integrate emotion and reason in the individual and collective construction of feelings and affections. Next, love is presented as a concept of analysis of the Social Sciences in the contributions of different disciplines that have enabled the interest of love as a social topic. Finally, the historical trajectory of love is presented as a concept from Classical Greece to contemporary visions of traditional patriarchal love and critical views on love as domination and power in its possibilities of change as the idea of love as a social and historical construction.